LIP FILLER WITH HYALURONIC ACID: CASE REPORT - Duarte Vieira Byrro, Daniella; Silvia Nogueira Garcia, Ana (Health and Society, 2022)
The present work addresses the technique of lip filling with Hyaluronic Acid (HA) in a dental office environment. For the elaboration of this article, a literature review was carried out, with searches in the following databases: SCIELO, PubMed, NLM. In addition, a clinical case of lip filling procedure with HA was performed using microcannula. This study aimed to present theoretical support on the safety and efficacy of using HA for the lip filling procedure, as well as to present the applicability of this technique for facial aesthetic treatment. The technique used improved the patient’s labial contour, offering greater volume to the lips. After 30 days there were no complications and the client showed a high degree of satisfaction with the procedure. The performance of lip filling with HA is a very popular procedure nowadays, patients who seek this procedure aim to improve the appearance of the lips, making them more voluminous and designed. It is a safe and minimally invasive procedure. Since HA is a substance that does not suffer rejection, it is a molecule naturally produced by fibroblasts present in the dermis.